Nanoscale design of polarization in ultrathin ferroelectric heterostructures - De Luca, Gabriele (Nat Commun, 2017)
The success of oxide electronics depends on the ability to design functional properties such as ferroelectricity with atomic accuracy. However, despite tremendous advances in ferroelectric heterostructures, the development towards multilevel architectures with precise layer-by-layer command over the polarization is impeded by the lack of continuous control over the balance of electrostatics, strain, chemistry and film thickness during growth. Moreover, the polarization in the deeper layers becomes inaccessible when these are buried by the ongoing deposition. Taking ferroelectric BaTiO(3) and multiferroic BiFeO(3) as model systems, we observe and engineer the emergence, orientation and interaction of ferroelectric polarization in ultrathin heterostructures with monolayer accuracy. We achieve this by optical second harmonic generation which tracks the evolution of spontaneous polarization in real time throughout the deposition process. Such direct and in situ access to the polarization during growth leads us to heterostructures with user-defined polarization sequences—towards a new class of functional ferroic materials.